2013
DOI: 10.1021/je3011776
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Solubility of CO2 in Aqueous Mixtures of DEA and AEEA

Abstract: The present communication presents the new experimental CO 2 solubility data in an aqueous mixture of diethanolamine (DEA) and (2-aminoethyl)ethanolamine (AEEA) at CO 2 concentrations in the inlet gas stream from (10.13 to 20.27) kPa and temperatures from (303.14 to 333.14) K. The aqueous (DEA + AEEA) mixtures of total concentrations were chosen from (0.92 to 3.22) mol·kg −1 , and the mole fraction of AEEA in total amine was varied from 0.02 to 0.20. The findings point that the CO 2 solubility in a fixed total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…Three gas temperatures were represented: 100, 125, and 150 • C. As can be seen, the carbon absorption decreases with the gas temperature due to a reduction in the Henry's constant. Previous works also revealed similar trends using ammonia [8] and other solvents such as DEA and AEEA [41]. Another effect that decreases carbon absorption is evaporation.…”
Section: Effect Of Evaporation and Temperaturesupporting
confidence: 72%
“…Three gas temperatures were represented: 100, 125, and 150 • C. As can be seen, the carbon absorption decreases with the gas temperature due to a reduction in the Henry's constant. Previous works also revealed similar trends using ammonia [8] and other solvents such as DEA and AEEA [41]. Another effect that decreases carbon absorption is evaporation.…”
Section: Effect Of Evaporation and Temperaturesupporting
confidence: 72%
“…AEEA shows proper absorption rate among amines that are added as an activator to the tertiary amines. Further, as it is a Diamine compound, one mole of it is able to absorb 2 moles of CO2, thus has a high absorption capacity for CO2 but it increases the regeneration cost [143]. Zoghi [144] considered five additives and reported that AEEA-MDEA aqueous solution has the highest absorption rate of CO2.…”
Section: Common Mixtures Of Aminesmentioning
confidence: 99%
“…The presence of potassium in solution increases the concentration of CO 3 2− /HCO 3 − in solution; therefore, solution has buffering property. These competing effects yield a maximum fraction of reactive species at potassium to piperazine ratio of 2 : 1 [ 75 , 83 , 84 ].…”
Section: Co 2 Separation Technologiesmentioning
confidence: 99%